2019
DOI: 10.1071/fp18323
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of cereal endosperm development with a focus on rice (Oryza sativa)

Abstract: The endosperm of cereal grain forms the staple diet for most of the world’s population, and feeds much of their stock. Grain size and quality are determined largely by events taking place during coenocytic nuclear division, endosperm cellularisation and cell differentiation, and the production of storage molecules. Thus, understanding the complex signalling processes occurring at each of these steps is essential for maintaining and improving our food supply. Here, we critically review evidence for the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 111 publications
0
25
0
Order By: Relevance
“…as evidenced in Joshi et al , ). Basunia and Nonhebel () also emphasized this issue of inadequate analyses with regard to auxin and cytokinin analyses.…”
Section: Cytokininsmentioning
confidence: 99%
“…as evidenced in Joshi et al , ). Basunia and Nonhebel () also emphasized this issue of inadequate analyses with regard to auxin and cytokinin analyses.…”
Section: Cytokininsmentioning
confidence: 99%
“…8A; Supplemental Table S5). Previous work has shown that ABCB4/11/14/22, DAO, GH3s, and IAAs are up-regulated in developing rice seeds at 24 HAF (Jain and Khurana, 2009;Uchiumi and Okamoto, 2010;French et al, 2014;Basunia and Nonhebel, 2019). TRYPTOPHAN AMINOTRANSFER-ASE-RELATED PROTEIN2 (TAR2), the auxin biosynthesis gene that is preferentially expressed prior to cellularization (Abu-Zaitoon et al, 2012), exhibited lower transcript levels in MADS78 and MADS79 mutants, while YUCCA7 was unaltered in the MADS78 mutant and showed higher transcript abundance in the MADS79 mutant (Fig.…”
Section: Expression Of Mads78 and Mads79 Is Negatively Associated Witmentioning
confidence: 95%
“…Early cellularization in the absence of MADS78 or MADS79 triggers activation of the CArG box-containing auxin biosynthesis genes YUCCA12 and TAR1 (Fig. 8A) that may have a role in subsequent endoreduplication, differentiation, and starch deposition during later stages of seed development (Abu-Zaitoon et al, 2012;Basunia and Nonhebel, 2019). Detection of CArG box-binding motifs in promoters of auxin biosynthesis enzyme-, transporter-, and signaling-related genes further supports the regulatory role of type I MADS box TFs in maintaining auxin levels and/or distribution (Supplemental Table S5).…”
Section: Interplay Between Auxin Type I Mads Box Tfs and Fis-prc2 Ementioning
confidence: 99%
“…Our RNA-seq analysis results, revealed that several auxin biosynthesis genes, including YUCs and TARs, were downregulated in grains of RGB1Ri lines either at 5 DAF or 10 DAF (Figure 3A). There is evidence that IAA plays several distinct roles at different stages of endosperm development (see review by Figueiredo and Köhler, 2018;Basunia and Nonhebel, 2019). These differing roles require strong localized control of IAA biosynthesis by specific enzymes.…”
Section: Rgb1 Stimulates Accumulation Of Iaa By Regulating the Expression Of Auxin Biosynthesis-related Genesmentioning
confidence: 99%